Hybrid CPFSK/OQPSK modulation transmission techniques’ performance efficiency with RZ line coding–based fiber systems in passive optical networks - Aadel M. Alatwi; Ahmed Nabih Zaki Rashed (Institute of Advanced Engineering and Science, 2021)
This study shows hybrid continuous-phase frequency shift keying (CPFSK)/optical quadrature-phase shift keying (OQPSK) modulation transmission techniques’ performance efficiency with return-to-zero (RZ) line coding scheme–based fiber systems in passive optical networks. Max. Q factor/min. bit error rate variations versus modulation frequency and fiber length are studied in detail for various bits/symbol, based on hybrid proposed modulation transmission techniques. Also, optical power and received electrical power variations are simulated with fiber-length variations at a specified modulation frequency of 300 GHz. Max. Q Factor, min. BER, max. signal power, and min. noise power variations are based on hybrid modulation techniques for CPFSK/OQPSK of 32 bits/symbol and a modulation frequency of 500 GHz through a fiber length of 30 km.